IDENTIFICATION OF PARACETAMOL AND COFFEINE IN TRADITIONAL MEDICINE BY HIGH PERFORMANCE LIQUID CHROMATOGRAPHY USING PHOTO DIODE ARRAY DETECTORS - Putri, Amelia; Sitorus, Saibun; Panggabean, Aman Sentosa; Sari, Ika Yekti Liana (PROSIDING SEMINAR KIMIA, 2023)
Traditional medicine is a supplement that can help maintain a healthy body which is produced from ingredients or ingredients derived from plants, so that it is still in great demand by the public because it is considered safe. Traditional medicinal preparations themselves are not allowed to contain Medicinal Chemicals (BKO). However, along with the increasing public interest, this has led to the circulation of traditional medicines containing BKO in order to obtain products with the fastest/ most effective effects. One of the chemical drugs that are often found are coffeine and paracetamol. This study aims to identify the medicinal chemicals of coffeine and paracetamol in traditional medicine using a solid phase extraction method which is then followed by high performance liquid chromatography with a photo diode array detector. The results obtained were that the coffeine standard produced a retention time of 5.791 with a wavelength of 206 nm and 272 nm while the paracetamol standard produced a retention time of 4.372 with a wavelength of 196 nm and 246 nm. The results of the analysis showed that the samples in the form of traditional medicines did not contain the medicinal chemicals coffeine and paracetamol Keywords: Coffeina, Paracetamol, Medicinal Chemicals, Traditional Medicine